PSMA and FDG-PET as predictive and prognostic biomarkers in patients given [177Lu]Lu-PSMA-617 versus cabazitaxel for metastatic castration-resistant prostate cancer (TheraP): a biomarker analysis from a randomised, open-label, phase 2 trial. Issue 11 (November 2022) - Buteau, James P; Martin, Andrew J; Emmett, Louise; Iravani, Amir; Sandhu, Shahneen; Joshua, Anthony M; Francis, Roslyn J; Zhang, Alison Y; Scott, Andrew M; Lee, Sze-Ting; Azad, Arun A; McJannett, Margaret M; et al.
Summary: Background: Previously, results from the TheraP trial showed that treatment with lutetium-177 [ 177 Lu]Lu-PSMA-617 improved frequency of prostate-specific antigen (PSA) response rate and progression-free survival compared with cabazitaxel in men with metastatic castration-resistant prostate cancer. In this study, we aimed to analyse gallium-68 [ 68 Ga]Ga-PSMA-11 PET (PSMA-PET) and 2-[ 18 F]fluoro-2-deoxy-D-glucose PET (FDG-PET) imaging parameters as predictive and prognostic biomarkers in this patient population. Methods: TheraP was a multicentre, open-label, randomised phase 2 trial that recruited men with metastatic castration-resistant prostate cancer after treatment with docetaxel who were suitable for cabazitaxel from 11 hospitals in Australia. Participants were required to be 18 years old or older; have adequate haematological, renal, and liver function; and an Eastern Cooperative Oncology Group performance status of 0–2. Participants were randomly assigned (1:1) using a centralised system using minimisation with a random component and that stratified patients by disease burden, previous treatment with enzalutamide or abiraterone, and study site. Patients were either given cabazitaxel (20 mg/m 2 intravenously every 3 weeks for up to ten cycles) or [ 177 Lu]Lu-PSMA-617 (6·0–8·5 GBq intravenously every 6 weeks for up to six cycles). The primary study endpoint, analysed previously, was PSA response rate. The prespecified tertiary study endpoint was association between total tumour quantitative parameters on PSMA-PET, FDG-PET, and baseline characteristics with clinical outcomes. A SUVmean of 10 or higher on PSMA-PET was evaluated as a predictive biomarker for response to [ 177 Lu]Lu-PSMA-617 versus cabazitaxel. A metabolic tumour volume (MTV) of 200 mL or higher on FDG-PET was tested as a prognostic biomarker. Both cutoff points were prespecified. The analysis was intention-to-treat, using logistic regression. This trial is registered with ClinicalTrials.gov, NCT03392428 . Findings: 200 patients were randomly assigned between Feb 6, 2018, and Sept 3, 2019. 101 men were assigned to the cabazitaxel group and 99 were assigned to the [ 177 Lu]Lu-PSMA-617 group. The median follow-up at data cutoff of July 20, 2020, was 18·4 months (IQR 12·8–21·8). 35 (35%) of 99 men who were assigned [ 177 Lu]Lu-PSMA-617 and 30 (30%) of 101 men who were assigned cabazitaxel had high PSMA uptake (SUVmean of ≥10). Odds of PSA response to [ 177 Lu]Lu-PSMA-617 versus cabazitaxel were significantly higher for men with SUVmean of 10 or higher compared with those with SUVmean of less than 10 (odds ratio [OR] 12·19 [95% CI 3·42–58·76] vs 2·22 [1·11–4·51]; padj =0·039 for treatment-by-SUVmean interaction). PSA response rate for [ 177 Lu]Lu-PSMA-617 compared with cabazitaxel was 32 (91% [95% CI 76–98]) of 35 men versus 14 (47% [29–65]) of 30 men in patients with SUVmean of 10 or higher, and 33 (52% [39–64]) of 64 men versus 23 (32% [22–45]) of 71 men in those with SUVmean of less than 10. High-volume disease on FDG-PET (MTV ≥200 mL) was seen in 30 (30%) of 99 men who were assigned [ 177 Lu]Lu-PSMA-617 and 30 (30%) of 101 men who were assigned cabazitaxel. PSA response rate for both treatment groups combined for FDG-PET MTV of 200 mL or higher versus FDG-PET MTV of less than 200 mL was 23 (38% [95% CI 26–52]) of 60 men versus 79 (56% [48–65]) of 140 men (OR 0·44, 95% CI 0·23–0·84; padj =0·035). Interpretation: In men with metastatic castration-resistant prostate cancer, PSMA-PET SUVmean was predictive of higher likelihood of favourable response to [ 177 Lu]Lu-PSMA-617 than cabazitaxel, which provides guidance for optimal [ 177 Lu]Lu-PSMA-617 use. High FDG-PET MTV was associated with lower responses regardless of randomly assigned treatment, warranting further research for treatment intensification. A strength of this analysis is the validation of pre-specified cutpoints within a multicentre, randomised, controlled trial. Quantitative PET parameters used, however, require specialised software and are not yet routinely available in most clinics. Funding: Prostate Cancer Foundation of Australia, Endocyte (a Novartis Company), Australian Nuclear Science and Technology Organisation, Movember Foundation, It's a Bloke Thing, CAN4CANCER, The Distinguished Gentleman's Ride.